Antihyperlipidemic and Antioxidant Activities of Ethanolic Extract of Paederia foetida Leaves (EEPFL) in Albino Rats (Sciences of Pharmacy, 2023)
The present study was designed to evaluate the antihyperlipidemic and antioxidant activities of leaves of Paederia foetida (EEPFL). The ethanolic extract was obtained by infusion method, and acute oral toxicity tests were performed according to Organization for Economic Cooperation and Development, 2006 (OECD) guidelines. Hyperlipidemia was induced by feeding the rats with a high-fat diet consisting of coconut oil and vanaspati ghee in a ratio of 2:3 v/v at a dose of 10 ml/kg body weight. The extract was given at a dose of 500mg/kg body weight. Total cholesterol, triglycerides, high-density lipoprotein (HDL), and low-density lipoprotein (LDL) cholesterol were measured for antihyperlipidemic activity. For antioxidant activity, Malondialdehyde (MDA), Catalase (CAT), and Superoxide Dismutase (SOD) were measured using standard methods. The extract showed a significant decrease in total cholesterol, triglycerides, LDL, and MDA in the blood. On the other hand, HDL, CAT, and SOD increased significantly. The study demonstrated that the ethanolic extract of leaves of Paederia foetida decreased blood lipid levels and lipid peroxidation. These findings suggest that the EEPFL may have potential therapeutic applications in the treatment of hyperlipidemia and oxidative stress-related diseases.